Pengaruh Strategi Pembelajaran Berbasis Masalah Terhadap Kemampuan Menulis Berita Kelas V SD Negeri 78 Barru Kecamatan Tanete Riaja Kabupaten Barru - Keisya Sashi Kirana; Rosmini Madeamin; Andi Syamsul Alam (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
The Influence of Problem-Based Learning Strategies on News Writing Ability for Class V of SD Negeri 78 Barru, Tanete Riaja District, Barru Regency. Thesis. Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I Rosmini Madeamain and Supervisor II Andi Syamsul Alam. This research aims to determine the significant influence of using problem-based learning strategies on the ability to write news for class V of SD Negeri 78 Barru, Tanete Riaja District, Barru Regency. This research is pre-experimental research in the form of One Group Pretest-Posttest research. The population of this study was class V students at SD Negeri 78 Barru which consisted of one class of 10 students. The research instrument used was the news writing test. The data obtained was then analyzed using descriptive statistical data analysis and inferential statistical data analysis. The results of this research show that the pretest results, the average student learning score is 53 with categories, very high 0%, high 30%, medium 20%, low 30% and very low 20%. The average score of the posttest results after using the problem-based learning strategy was 88 with the categories very high 80%, high 20%, medium 0%, low 0%, and very low 0%. This figure shows that there is a significant influence of the use of problem-based learning strategies on news writing ability. Based on the description above, it can be concluded that the problem-based learning strategy is effectively used in learning to write news for fifth grade students at SD Negeri 78 Barru, Tanete Riaja District, Barru Regency.